Effect of surface temperature on soil moisture retrieval using CYGNSS - Yifan Zhu; Fei Guo; Xiaohong Zhang (International Journal of Applied Earth Observations and Geoinformation, 2022)
In this paper, a soil moisture (SM) retrieval model from spaceborne Global Navigation Satellite System Reflectometry (GNSS-R) observations that incorporates soil surface temperature (SST) for the first time is evaluated. Here, based on the grid scale, Cyclone GNSS (CYGNSS) reflectivity, SST and vegetation optical depth (VOD) are employed to estimate SM by a trilinear regression, while the other influence factors such as soil roughness and texture are regard as static. The results are compared with globally Soil Moisture Active Passive (SMAP) SM and in-situ measurements from International Soil Moisture Network (ISMN) over the year of 2018 respectively, showing a good consistency (R = 0.929 and RMSE = 0.043 cm3cm−3 against SMAP SM; R = 0.927 and RMSE = 0.042 cm3cm−3 against in-situ SM). Although the sensitivity of reflectivity to SST is found to be much smaller than that to SM from the simulation, the incorporation of SST is demonstrated to be effective in SM estimation for its coupling relationship with SM. In the comparison with SMAP SM, the improvements of RMSE by incorporating SST are varying degrees globally, and significant in many arid areas with an improvement of over 40%. In the in-situ validation, the overall RMSE decreases from 0.047 to 0.042 cm3cm−3 with an improvement of 10.6%. This work demonstrates the necessity and improvement for incorporating SST into SM retrieval for GNSS-R. Moreover, the findings provide a potential method to obtain global SST dataset from CYGNSS observations.